AN ANALYSIS OF USING NOMINALIZATION IN ACADEMIC ABSTRACTS - khasanah, Zumrotul (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2024)
AbstractAcademic writing have an abstract to show what the writer wrote in quickly. In academic writing, many information attendant complexity of language which known as nominalization, or grammatical metaphor (Halliday, 1985) where verbs and adjectives are realized as nouns. As a result, based the theory above, this paper aims to analysis the realization of using nominalization in academic abstracts. In this paper the researcher calculate nominalizations in 8 academic abstracts. By manual sorting and also adopting a mixture of qualitative and quantitative methods.